Network Congestion Estimation and Analysis in Vehicular Networks - Figueiredo, Andreia; Luis, Miguel; Rito, Pedro; Sargento, Susana (Proceedings of the ... IEEE Workshop on Local and Metropolitan Area Networks, 2025)
The rapid expansion of vehicular networks is expected to cause significant congestion in communication channels, potentially compromising the reliability of safety and traffic management systems. To mitigate congestion, the European Telecommunications Standards Institute (ETSI) developed the Decentralized Congestion Control (DCC) mechanism, which dynamically adjusts transmission parameters based on real-time channel conditions. However, real-time DCC data may not always be available due to hardware limitations. This paper proposes a new approach to estimate the Channel Busy Ratio (CBR) in ITS-G5 vehicular networks through passive channel observation. Using real hardware, we compare the proposed estimator with measurements from the wireless card, showing a maximum error below 5.6%. We also analyze the impact of standard vehicular messages and IP traffic on network congestion. The estimator offers accurate, non-intrusive CBR measurements, supporting congestion control where direct measurement is impractical.